Analysis of semiconductor quantum generators of A3B5 type at nano levels - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The article describes the formation of the cluster grid structure ofsemiconductor crystals of A3B5 type.The deformation of the electron shells of the atoms in semiconductorcrystal structure elements has been presented. Crystals of theIndium compounds and the elements from Group 5 of the Mendeleevperiodic table have been used to show the energy levels where a semiconductorquantum generator is generated. The technological conditionsfor an A3B5 type laser realisation have been defined.
Keywords: semiconductor laser; nanocluster level; generation